Interview with Alex Zucker for Translation Review. (2nd January 2019) - Unknown
Abstract : Jonathan Becker was a research assistant at the Center for Translation Studies at the University of Texas at Dallas from 2015 to 2018. In 2017, he earned his Masters from UT Dallas with a translation of the contemporary German author Marcel Beyer. He currently lives in his native Berlin. Alex Zucker is an award-winning translator of prose and drama from the Czech. He served as a co-chair of the PEN America Translation Committee from 2014 to 2016 and is currently working with the Authors Guild to develop a model contract for literary translators. The Czech authors he has translated include Jáchym Topol, Magdaléna Platzová, Tomáš Zmeškal, Heda Margolius Kovály, and Josef Jedlička. His latest translations are Three Plastic Rooms by Petra Hůlová and Society for the Prevention of Cruelty to Animals by J. R. Pick. This interview was conducted in December 2017 at Zucker's home in Brooklyn.